160k views
5 votes
Choose the inverse of y=X2-2

User Akhikhl
by
5.5k points

2 Answers

1 vote

Answer:

26

Explanation:

User Mariama
by
5.5k points
3 votes

For this case we must find the inverse of the following function:


y = x ^ 2-2

We exchange the variables:


x = y ^ 2-2

We clear the variable "y":

Adding 2 to both sides we have:


x + 2 = y ^ 2

Applying square root on both sides of the equation:


y = \pm \sqrt {x + 2}

We change y by
f ^ {- 1} (x):
f ^ {- 1} (x) =\pm \sqrt {x + 2}

Answer:


f ^ {- 1} (x) = \pm\sqrt {x + 2}

User Irineu Antunes
by
5.0k points